(untitled) (Research, Society and Development, 2022)
Soybean seeds early treatment practiceractice of early treatment of soybean seeds can be harmful to the physiological quality, due to the potential phytotoxic effect. Thus, the objective was to verify chemical treatment effect on soybean seeds physiological quality when submitted to different storage periods. The design used was completely randomized, in a 2x2x5 factorial scheme, that is, two soybean cultivars (NS6906 IPRO and NS7667 IPRO), two chemical seed treatments (control and treated with fungicide and insecticide) and five storage periods (0; 15; 30; 45 and 60 days), with four replications wiht 50 seeds each. Parameters evaluated in germination test were: first count and germination percentage, germination speed index, average time and germination speed, while in emergency test they were percentage and emergence speed index and, finally, electric conductivity. The storage period of soybean seeds had a negative effect on their vigor and quality, and this factor maximized its effects when combined with the chemical treatment of the seeds with insecticide and fungicide, especially after 30 days of storage. The chemical treatment of seeds, in general, was harmful to electrical conductivity, percentage of emergence, average speed and average germination time. The cultivar NS6906 showed the worst response to the storage period and to the chemical treatment of the seeds, with NS7667 having the highest tolerance to storage conditions, therefore, indicated for early treatment.